Existential Crisis Of The Poet Character In "Al Shaʿir" By Taufiq Al-Hakim: A Literary Psychology Study Based On Viktor Frankl's Logotherapy - H., Muh Arya Satya (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study analyzes the theme of the poet character facing an existential crisis in Taufiq al-Hakim's al-Shaʿir from a perspective of literary psychology, especially Viktor Frankl's logotherapy. By employing artistic expression into this particular life, the poet negotiates between personal creativity and social expectation. The research uses a qualitative-descriptive approach with close textual analysis of the original Arabic text, checking character development, internal monologues, and narrative symbolism. Based on Frankl’s triadic order of will to meaning, freedom of will and meaning of life dimensions, this research reveals not only the inner conflicts and the choice but also that Montmartre is a canvas in which an artist outside explores his creativity. Results indicate that the poet's search for existential meaning is demonstrated through his preference for matters of art over actual living, stocktaking on what constitutes human purpose; and seeking drive-through creativity and fulfillment. This study serves as a contribution to the understanding of modern Arabic literature and demonstrates an application of existential psychology in literary analysis at large, so that more works can be explored through the lens of personal purpose as expressed artistically.